Reproduction of Saccodon dariensis (Teleostei: Parodontidae) in Guatapé River tributaries, Magdalena River basin, Colombia. - Mancera-Rodríguez, Néstor Javier; Castellanos-Barliza, Jeiner; Urrego-Ballestas, Diego Alejandro (Revista de Biología Tropical, 2016)
The Andean mountain region of Colombia has a high diversity of fish, with high number of endemic species. To promote their protection and conservation, the knowledge of their general and reproductive biology is necessary. With this aim, the reproductive biology of Saccodon dariensis, in the Peñoles and El Cardal creeks, Guatape River mid-basin, Magdalena River Basin, was studied, to determine reproductive differences between individuals with different oral polymorphism (morpho I vs. morpho IV, according to Roberts, 1974), and to define a possible spatial or temporal reproductive isolation. Ten field samplings were carried out between October 2007 and February 2012, in periods of rain (October and November 2007, May 2008 and November 2011), dry (January and March 2010, February 2012), transition from rain to dry (June 2011) and transition from dry to rain (March 2008 and September 2011). Samples were caught using electrofishing equipment and cast nets (10 mm between knots). A total of 468 specimens were analyzed, 268 of which were females and 200 males. The average catch size for the total number of individuals studied was 109.6 mm SL (65.5-174.0 mm), with 108.0 mm SL for females (67.7-174.0) and 111.9 mm SL (65.5-149.4) for males. Females predominated in the catches, and the sex ratio of 1.0:1.34 significantly deviated from the theoretical distribution 1:1. Similarly, morpho IV predominated in the catches, and morphs ratio was 1.00:1.48. Based on the monthly evolution of the gonadosomatic index (GSI) and the proportion of mature specimens, the spawning season occurs during periods of transition from dry to rainy season when water level begins to raise. The lowest values of the condition factor that match the maximum values of GSI, indicates that this species accumulated body energy reserves that are used during the gonadal maturation and spawning. The mean size at sexual maturity (L50) was 88.8 mm SL in females and 109.3 mm SL in males. The fecundity of S. dariensis fluctuated between 1 137 and 39 303 (mean = 8 309, SD = 9 021) and the relative fecundity between 144 and 1 131 oocytes/g of total weight (mean = 439 ± 212). The diameter of the oocytes was 0.54 mm (SD = 0.07). Different development in oocytes was not observed, suggesting massive spawning. The coexistence of the two morphs, external fertilization and simultaneous occurrence of reproductive peaks found in this study did not provide support for a possible spatial or temporal reproductive isolation of morphotypes.